TONER, TONER CONTAINING UNIT, IMAGE FORMING APPARATUS, AND IMAGE FORMING METHOD
Patent Information
- Application Number
- JP2021073221
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-04-23
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2041-04-23
AI Technical Summary
【0009】 本発明の一態様によれば、耐オフセット性及び色再現性に優れるトナーを提供することができる。
Smart Images

Figure 0007632027000002 
Figure 0007632027000003 
Figure 0007632027000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a toner, a toner storage unit, an image forming apparatus, and an image forming method. [Background technology]
[0002] In recent years, there has been a demand for toners that have a reduced environmental impact. To meet this demand, for example, reductions in the amount of energy and chemicals used in the toner manufacturing process and reductions in power consumption by improving the low-temperature fixability of the toner itself have been considered.
[0003] The toner was produced by pulverization, but due to the large amount of energy required for production and the trend towards smaller toner particles, chemical toners produced by suspension polymerization, etc., are becoming mainstream. In addition, a method for improving the low-temperature fixing property of toners is known, such as introducing a crystalline resin into the binder resin.
[0004] One method for improving the offset resistance of a toner is to adjust the viscoelasticity of the toner. Specifically, a method has been proposed in which a resin with high crystallinity is introduced into the binder resin of the toner to control the viscoelasticity to a specific value (see, for example, Patent Document 1).
[0005] In addition, a method has been proposed for providing a toner that is excellent in hot offset properties and mechanical durability by adjusting the molar ratio of polyhydric alcohol-derived atomic groups in the polyester resin component contained in the binder resin of the toner (see, for example, Patent Document 2). Summary of the Invention [Problem to be solved by the invention]
[0006] However, it has been found that the toner obtained by the conventional method is insufficient in terms of offset resistance and color reproducibility.
[0007] An object of the present invention is to provide a toner having excellent offset resistance and color reproducibility. [Means for solving the problem]
[0008] In order to solve the above-mentioned problems, one aspect of the present invention is a method for producing a binder resin comprising the steps of: a toner comprising: a binder resin containing a crystalline polyester resin; and a content of the crystalline polyester resin in the toner is 20% by mass or less; The toner is characterized in that the curve of the storage modulus G' measured in dynamic viscoelasticity measurement has a maximum value in the range of 100° C. or higher. Effect of the Invention
[0009] According to one aspect of the present invention, a toner having excellent offset resistance and color reproducibility can be provided. [Brief description of the drawings]
[0010] [Figure 1] Graph showing a measurement curve of storage elastic modulus. [Diagram 2] FIG. 1 illustrates an example of an image forming apparatus. [Diagram 3] FIG. 13 is a diagram showing another example of an image forming apparatus. [Figure 4] FIG. 4 is a partial enlarged view of the image forming apparatus of FIG. 3. [Diagram 5] FIG. 2 illustrates an example of a process cartridge. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, an embodiment of the present invention will be described.
[0012] <Toner> The toner according to the present embodiment contains a binder resin and a metal crosslinking agent that forms a metal bridge with the binder resin, and the measurement curve of the storage modulus G' in dynamic viscoelasticity measurement has a maximum value in the range of 100° C. or more. Hereinafter, an example of the toner according to the present embodiment containing base particles and external additives will be described.
[0013] [Base particle] The base particles refer to particles that constitute the base that becomes the core of the toner (hereinafter, may be referred to as the toner base or the toner base particles). The toner base contains a binder resin and a coagulating salt.
[0014] [Binding resin] The binder resin is an example of the binder resin contained in the toner of the present embodiment. The binder resin is not particularly limited, but preferably contains a crystalline resin or an amorphous resin. The crystalline resin preferably contains a crystalline polyester resin. The amorphous resin preferably contains an amorphous polyester resin.
[0015] [Crystalline polyester resin] The melting point of the crystalline polyester resin is preferably in the range of 50°C or more and 100°C or less, more preferably in the range of 55°C or more and 90°C or less, and even more preferably in the range of 55°C or more and 85°C or less.
[0016] When the melting point of the crystalline polyester resin is 50° C. or higher, blocking does not occur in the stored toner, and the toner storage properties and the fixed image storage properties after fixing are improved. Furthermore, sufficient low-temperature fixability can be obtained by having the melting point of the crystalline polyester resin be 100° C. or less. The melting point of the crystalline polyester resin is determined as the peak temperature of the endothermic peak obtained by differential scanning calorimetry (DSC).
[0017] The crystalline polyester resin in this embodiment includes not only polymers having a 100% polyester structure, but also copolymers of monomers constituting polyester with other monomers, provided that the proportion of the other monomers in the copolymers is 50% by weight or less.
[0018] The crystalline polyester resin used in the toner of the present embodiment is synthesized from, for example, a polyvalent carboxylic acid and a polyhydric alcohol. Note that, as the crystalline polyester resin, a commercially available product or a synthesized product may be used.
[0019] Examples of polyvalent carboxylic acids include aliphatic dicarboxylic acids such as oxalic acid, maleic acid, fumaric acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, 1,18-octadecanedicarboxylic acid, and mesaconic acid; aromatic dicarboxylic acids such as phthalic acid, isophthalic acid, terephthalic acid, naphthalene-2,6-dicarboxylic acid, malonic acid, trimellitic acid, and naphthalenedicarboxylic acid; alicyclic carboxylic acids such as cyclohexanedicarboxylic acid; anhydrides thereof; and lower alkyl esters thereof.
[0020] Examples of trivalent or higher carboxylic acids include pyromellitic acid, 1,2,4-benzenetricarboxylic acid, 1,2,5-benzenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, and the like, as well as their anhydrides and lower alkyl esters, etc. These may be used alone or in combination of two or more.
[0021] The polycarboxylic acid may contain, as other carboxylic acids, a dicarboxylic acid having a sulfonic acid group, and may further contain a dicarboxylic acid having a double bond.
[0022] The polyhydric alcohol is preferably an aliphatic diol, more preferably a straight-chain aliphatic diol having 7 to 20 carbon atoms in the main chain, and even more preferably a straight-chain aliphatic diol having 14 or less carbon atoms in the main chain.
[0023] In the case of branched aliphatic diols, the crystallinity of the polyester resin may decrease, lowering the melting point. In addition, if the carbon number of the main chain is less than 7, the melting temperature becomes high when polycondensed with aromatic dicarboxylic acid, and low-temperature fixing may become difficult. On the other hand, if the carbon number of the main chain is more than 20, it becomes difficult to obtain a practical material.
[0024] The content of the aliphatic diol in the polyhydric alcohol is preferably 80 mol % or more, more preferably 90 mol % or more. If it is less than 80 mol %, the crystallinity of the polyester resin decreases and the melting temperature drops, which may result in deterioration of toner blocking resistance, image storage stability, and low-temperature fixability.
[0025] Examples of the aliphatic diol include aliphatic diols such as ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, neopentyl glycol, 1,2-hexanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,14-eicosanedecanediol; alicyclic diols such as cyclohexanediol, cyclohexanedimethanol, and hydrogenated bisphenol A; and aromatic diols such as an ethylene oxide adduct of bisphenol A and a propylene oxide adduct of bisphenol A. Among these, 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol are preferable in consideration of availability.
[0026] Examples of trihydric or higher alcohols include glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, etc. These may be used alone or in combination of two or more.
[0027] If necessary, for the purpose of adjusting the acid value or hydroxyl value, the polyvalent carboxylic acid or polyhydric alcohol may be added at the final stage of the synthesis.
[0028] The crystalline polyester resin can be produced at a polymerization temperature of 180° C. to 230° C., and the reaction is carried out while reducing the pressure in the reaction system as necessary and removing water and alcohol generated during condensation. If the monomer is not soluble or compatible at the reaction temperature, a high-boiling point solvent may be added as a dissolution aid to dissolve the monomer.
[0029] The polycondensation reaction is carried out while distilling off the solubilizing agent. When a monomer having poor compatibility is present in the copolymerization reaction, it is preferable to condense the monomer having poor compatibility with the acid or alcohol to be polycondensed in advance and then polycondense the monomer with the main component.
[0030] Examples of catalysts that can be used in producing the polyester resin include alkali metal compounds such as sodium and lithium; alkaline earth metal compounds such as magnesium and calcium; metal compounds such as zinc, manganese, antimony, titanium, tin, zirconium, and germanium; phosphorous compounds; phosphoric acid compounds; and amine compounds.
[0031] Specific examples of the compounds include sodium acetate, sodium carbonate, lithium acetate, lithium carbonate, calcium acetate, calcium stearate, magnesium acetate, zinc acetate, zinc stearate, zinc naphthenate, zinc chloride, manganese acetate, manganese naphthenate, titanium tetraethoxide, titanium tetrapropoxide, titanium tetraisopropoxide, titanium tetrabutoxide, antimony trioxide, triphenylantimony, tributylantimony, tin formate, tin oxalate, tetraphenyltin, dibutyltin dichloride, dibutyltin oxide, diphenyltin oxide, zirconium tetrabutoxide, zirconium naphthenate, zirconyl carbonate, zirconyl acetate, zirconyl stearate, zirconyl octylate, germanium oxide, triphenyl phosphite, tris(2,4-di-t-butylphenyl)phosphite, ethyltriphenylphosphonium bromide, triethylamine, and triphenylamine.
[0032] These crystalline polyester resins may be used alone or in combination of two or more.
[0033] The content of the crystalline polyester resin in the toner is usually 3% by mass or more and 20% by mass or less, and preferably 5% by mass or more and 15% by mass or less. When the content of the crystalline polyester resin in the toner is 3% by mass or more, the low-temperature fixing property of the toner can be improved, and when the content is 20% by mass or less, the heat-resistant storage stability of the toner can be improved and the occurrence of fogging of the image can be suppressed.
[0034] [Non-crystalline polyester resin] Examples of the non-crystalline polyester resin include modified polyester resins and unmodified polyester resins, and it is preferable to use both.
[0035] [Modified polyester resin] The modified polyester resin may be, for example, a polyester having an isocyanate group. The polyester prepolymer (A) having an isocyanate group may be a polycondensate of a polyol (1) and a polycarboxylic acid (2), which is a polyester having an active hydrogen group, and further reacted with a polyisocyanate (3).
[0036] Examples of the active hydrogen group contained in the polyester include a hydroxyl group (an alcoholic hydroxyl group and a phenolic hydroxyl group), an amino group, a carboxyl group, and a mercapto group. Among these, an alcoholic hydroxyl group is preferred.
[0037] The polyol (1) includes a diol (1-1) and a trihydric or higher polyol (1-2), and (1-1) alone or a mixture of (1-1) and a small amount of (1-2) is preferred.
[0038] Examples of the diol (1-1) include alkylene glycols (ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,6-hexanediol, etc.); alkylene ether glycols (diethylene glycol, triethylene glycol, dipropylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene ether glycol, etc.); alicyclic diols (1,4-cyclohexanedimethanol, hydrogenated bisphenol A, etc.); bisphenols (bisphenol A, bisphenol F, bisphenol S, etc.); alkylene oxide (ethylene oxide, propylene oxide, butylene oxide, etc.) adducts of the above alicyclic diols; and alkylene oxide (ethylene oxide, propylene oxide, butylene oxide, etc.) adducts of the above bisphenols.
[0039] Among these, alkylene glycols having 2 to 12 carbon atoms and alkylene oxide adducts of bisphenols are preferred, and alkylene oxide adducts of bisphenols and combinations thereof with alkylene glycols having 2 to 12 carbon atoms are more preferred.
[0040] Examples of the trihydric or higher polyol (1-2) include polyhydric aliphatic alcohols having a hydric or higher valence and an octahydric or higher valence (glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, sorbitol, etc.); trihydric or higher phenols (trisphenol PA, phenol novolac, cresol novolac, etc.); and alkylene oxide adducts of the above trihydric or higher polyphenols.
[0041] The polycarboxylic acid (2) may be a dicarboxylic acid (2-1) or a tri- or higher carboxylic acid (2-2). Preferred is (2-1) alone or a mixture of (2-1) and a small amount of (2-2).
[0042] Examples of the dicarboxylic acid (2-1) include alkylene dicarboxylic acids (succinic acid, adipic acid, sebacic acid, etc.), alkenylene dicarboxylic acids (maleic acid, fumaric acid, etc.), aromatic dicarboxylic acids (phthalic acid, isophthalic acid, terephthalic acid, naphthalene dicarboxylic acid, etc.), etc. Among these, alkenylene dicarboxylic acids having 4 to 20 carbon atoms and aromatic dicarboxylic acids having 8 to 20 carbon atoms are preferred.
[0043] Examples of the trivalent or higher polycarboxylic acid (2-2) include aromatic polycarboxylic acids having 9 to 20 carbon atoms (e.g., trimellitic acid, pyromellitic acid, etc.). The polycarboxylic acid (2) may be the above-mentioned acid anhydride or lower alkyl ester (e.g., methyl ester, ethyl ester, isopropyl ester, etc.).
[0044] The ratio of polyol (1) to polycarboxylic acid (2), expressed as the equivalent ratio [OH] / [COOH] of the hydroxyl group [OH] to the carboxyl group [COOH], is usually 2 / 1 to 1 / 1, preferably 1.5 / 1 to 1 / 1, and more preferably 1.3 / 1 to 1.02 / 1.
[0045] Examples of the polyisocyanate (3) include aliphatic polyisocyanates (tetramethylene diisocyanate, hexamethylene diisocyanate, 2,6-diisocyanatomethyl caproate, etc.); alicyclic polyisocyanates (isophorone diisocyanate, cyclohexylmethane diisocyanate, etc.); aromatic diisocyanates (tolylene diisocyanate, diphenylmethane diisocyanate, etc.); araliphatic diisocyanates (α,α,α',α'-tetramethylxylylene diisocyanate, etc.); isocyanurates; and those obtained by blocking the above-mentioned polyisocyanates with phenol derivatives, oximes, caprolactam, etc.
[0046] These non-crystalline polyester resins may be used alone or in combination of two or more.
[0047] The ratio of polyisocyanate (3) is usually 5 / 1 to 1 / 1, preferably 4 / 1 to 1.2 / 1, and more preferably 2.5 / 1 to 1.5 / 1, in terms of the equivalent ratio [NCO] / [OH] of the isocyanate group [NCO] to the hydroxyl group [OH] of the polyester having a hydroxyl group. If [NCO] / [OH] exceeds 5, low-temperature fixing property deteriorates. If the molar ratio of [NCO] is less than 1, the urea content in the modified polyester decreases, and hot offset resistance deteriorates.
[0048] The content of polyisocyanate (3) in the polyester prepolymer (A) having an isocyanate group at its end is usually 0.5% by weight or more and 40% by weight or less, preferably 1% by weight or more and 30% by weight or less, and more preferably 2% by weight or more and 20% by weight or less. If it is less than 0.5% by weight, the hot offset resistance is deteriorated and it is disadvantageous in terms of achieving both heat resistant storage stability and low temperature fixability. If it exceeds 40% by weight, the low temperature fixability is deteriorated.
[0049] The number of isocyanate groups contained per molecule in the polyester prepolymer (A) having an isocyanate group is usually at least 1, preferably an average of from 1.5 to 3, more preferably an average of from 1.8 to 2.5. If there is less than 1 isocyanate group per molecule, the molecular weight of the modified polyester after crosslinking and / or elongation is low, and the hot offset resistance is deteriorated.
[0050] [Unmodified polyester resin] In this embodiment, it is preferable to use not only the modified polyester prepolymer (A) alone but also the unmodified polyester (C) as a toner binder component together with the polyester prepolymer (A). By using the polyester (C) in combination, the low-temperature fixability and the gloss and gloss uniformity when used in a full-color device are improved.
[0051] Examples of the polyester (C) include a polycondensate of a polyol (1) and a polycarboxylic acid (2) similar to the polyester component of the polyester prepolymer (A) described above, and preferably a polyester having an active hydrogen group further reacted with a polyisocyanate (3).
[0052] The polyester (C) may be not only an unmodified polyester, but also one modified with a chemical bond other than a urea bond, for example, one modified with a urethane bond.
[0053] It is preferable that the polyester prepolymer (A) and the polyester (C) are at least partially compatible with each other in terms of low temperature fixing property and hot offset resistance, and therefore it is preferable that the polyester component of the polyester prepolymer (A) and (C) have similar compositions.
[0054] When the polyester prepolymer (A) is contained, the weight ratio of the polyester prepolymer (A) to (C) is usually 5 / 95 to 75 / 25, preferably 10 / 90 to 25 / 75, more preferably 12 / 88 to 25 / 75, and further preferably 12 / 88 to 22 / 78. If the weight ratio of the polyester prepolymer (A) is less than 5%, the hot offset resistance is deteriorated and it is disadvantageous in terms of achieving both heat resistant storage stability and low temperature fixability.
[0055] The peak molecular weight of the polyester (C) is usually from 1000 to 30000, preferably from 1500 to 10000, and more preferably from 2000 to 8000. If it is 1000 or more, deterioration of heat-resistant storage stability is suppressed, and if it is 10000 or less, deterioration of low-temperature fixability is suppressed.
[0056] The hydroxyl value of the polyester (C) is preferably 5 or more, more preferably 10 to 120, and further preferably 20 to 80. A hydroxyl value of 5 or more is advantageous in terms of achieving both heat-resistant storage stability and low-temperature fixability.
[0057] The acid value of the polyester (C) is usually 0.5 to 40, preferably 5 to 35. The acid value tends to make the toner negatively chargeable. When the acid value and hydroxyl value are within the above ranges, the toner is less susceptible to environmental influences under high temperature and high humidity conditions, and low temperature and low humidity conditions, and image deterioration is suppressed.
[0058] The content of the amorphous polyester resin in the toner is usually 50 to 90% by mass, and preferably 60 to 80% by mass. When the content of the amorphous polyester A in the toner is 50% by mass or more, the occurrence of fog and distortion of an image can be suppressed, and when it is 90% by mass or less, the low-temperature fixability of the toner can be improved.
[0059] [Coagulated salt] The coagulated salt forms a metal bridge with the binder resin, and is an example of a metal cross-linking agent contained in the toner of the present embodiment.
[0060] The viscoelasticity of the toner according to the present embodiment can be controlled by the type of coagulating salt added in the coagulation process described below and the acid value of the polyester resin constituting the toner. The storage modulus of the toner described below is proportional to the abundance ratio of the metal salt contained in the coagulating salt, such as magnesium, to the carboxyl group contained in the polyester resin in the toner, and the higher the ratio of the metal salt to the carboxyl group, the higher the viscoelasticity of the toner.
[0061] The reason for this is believed to be that the carboxyl group chelates with magnesium ions, which are polyvalent metal ions, to form metal bridges, which increase the crosslink density. In addition, compared to a method of controlling viscoelasticity by covering a core resin with a silicon shell, such as suspension polymerization, the viscoelasticity of the core resin can be controlled uniformly, so that a more stable viscoelasticity of the toner can be expressed.
[0062] The coagulant preferably contains a monovalent or higher metal salt from the viewpoint of ensuring sufficient crosslinking density. The monovalent or higher metal salt contained in the coagulant is preferably a divalent metal salt, more preferably a trivalent metal salt. As the coagulant, a known one can be used, for example, a metal salt of a monovalent metal such as sodium or potassium, a metal salt of a divalent metal such as calcium or magnesium, or a metal salt of a trivalent metal such as iron or aluminum.
[0063] These coagulated salts may be used alone or in combination of two or more.
[0064] [Method for evaluating metal salts present in toner] In the present embodiment, the quantitative analysis of the metal salt contained in the toner is preferably carried out by the following method.
[0065] That is, 1 ppm of toner is dissolved in each of xylene, ethanol, and chloroform to prepare sample solutions, and each sample solution can be analyzed (N=5) by an ICP emission spectrometer (SPS-3100, manufactured by Seiko Instruments).
[0066] The measurement conditions are as follows. High frequency output: 1.6kW Plasma gas flow rate: 18L / min Auxiliary gas flow rate: 1.5L / min Carrier gas flow rate: 0.1MPa Integration times: 3 ·Integration time: 2 seconds Photometric height: 12mm
[0067] In the toner of the present embodiment, the agglomerated salt (metal crosslinking agent) contained in the toner matrix contains a monovalent or higher metal salt as described above, thereby increasing the crosslink density of the binder resin in the toner matrix and improving the viscoelasticity of the binder resin, thereby stabilizing the viscoelasticity of the toner and improving the offset resistance.
[0068] The toner base may further contain other components as necessary, such as a colorant, a release agent, and a charge control agent.
[0069] [Coloring agent] The colorant is not particularly limited and can be appropriately selected according to the purpose. Examples of the colorant include carbon black, nigrosine dye, iron black, naphthol yellow S, Hansa yellow (10G, 5G, G), cadmium yellow, yellow iron oxide, yellow ochre, yellow lead, titanium yellow, polyazo yellow, oil yellow, Hansa yellow (GR, A, RN, R), pigment yellow L, benzidine yellow (G, GR), permanent yellow (NCG), Balkan fast yellow (5G, R), tartrazine lake, quinoline yellow lake, anthrazan yellow BGL, isoindolinone yellow, red iron oxide, lead, Red, vermilion, cadmium red, cadmium mercury red, antimony vermilion, permanent red 4R, para red, physey red, parachloro orthonitroaniline red, lithol fast scarlet G, brilliant fast scarlet, brilliant carmine BS, permanent red (F2R, F4R, FRL, FRLL, F4RH), fast scarlet VD, belkam fast rubin B, brilliant scarlet G, lithol rubin GX, permanent red F5R, brilliant carmine 6B, pigment Toscarlet 3B, Bordeaux 5B, Toluidine Maroon, Permanent Bordeaux F2K, Helio Bordeaux BL, Bordeaux 10B, Bon Maroon Light, Bon Maroon Medium, Eosin Lake, Rhodamine Lake B, Rhodamine Lake Y, Alizarin Lake, Thioindigo Red B, Thioindigo Maroon, Oil Red, Quinacridone Red, Pyrazolone Red, Polyazo Red, Chrome Vermilion, Benzidine Orange, Perinone Orange, Oil Orange, Cobalt Blue, Cerulean Blue, Alkaline Blue Lake, Pea Cocks Blue Lake, Victoria Blue Lake, Metal-free Phthalocyanine Blue, Phthalocyanine Blue, Fast Sky Blue, Indanthrene Blue (RS, BC), Indigo, Ultramarine Blue, Prussian Blue, Anthraquinone Blue, Fast Violet B, Methyl Violet Lake, Cobalt Purple, Manganese Purple, Dioxane Violet, Anthraquinone Violet, Chrome Green, Zinc Green, Chromium Oxide, Pyridian, Emerald Green, Pigment Green B, Naphthol Green B, Green Gold, Acid Green Lake,Examples include malachite green lake, phthalocyanine green, anthraquinone green, titanium oxide, zinc oxide, and lithopone.
[0070] These colorants may be used alone or in combination of two or more.
[0071] The content of the colorant is not particularly limited and can be appropriately selected depending on the purpose. The content of the colorant is, for example, preferably 1% by mass to 15% by mass, more preferably 3% by mass to 10% by mass, based on 100% by mass of the toner.
[0072] The colorant can also be used as a master batch in which the colorant is combined with a resin.
[0073] Examples of resins to be used in the preparation of a masterbatch or to be kneaded with a masterbatch include, in addition to the above-mentioned amorphous polyester resins, polymers of styrene or its substitutes, such as polystyrene, poly-p-chlorostyrene, and polyvinyltoluene; styrene-p-chlorostyrene copolymers, styrene-propylene copolymers, styrene-vinyltoluene copolymers, styrene-vinylnaphthalene copolymers, styrene-methyl acrylate copolymers, styrene-ethyl acrylate copolymers, styrene-butyl acrylate copolymers, styrene-octyl acrylate copolymers, styrene-methyl methacrylate copolymers, styrene-ethyl methacrylate copolymers, styrene-butyl methacrylate copolymers, and styrene-α-chloromethyl methacrylate copolymers. copolymers such as styrene-based copolymers, styrene-acrylonitrile copolymers, styrene-vinyl methyl ketone copolymers, styrene-butadiene copolymers, styrene-isoprene copolymers, styrene-acrylonitrile-indene copolymers, styrene-maleic acid copolymers, and styrene-maleic acid ester copolymers; polymethyl methacrylate, polybutyl methacrylate, polyvinyl chloride, polyvinyl acetate, polyethylene, polypropylene, polyester, epoxy resins, epoxy polyol resins, polyurethane, polyamide, polyvinyl butyral, polyacrylic acid resins, rosin, modified rosin, terpene resins, aliphatic or alicyclic hydrocarbon resins, aromatic petroleum resins, chlorinated paraffin, and paraffin wax. These may be used alone or in combination of two or more.
[0074] The master batch can be obtained by mixing and kneading a resin for the master batch and a colorant under high shear force, in which case an organic solvent can be used to enhance the interaction between the colorant and the resin.
[0075] Also, a method called the flushing method can be used in which an aqueous paste containing a water-containing colorant is mixed and kneaded with a resin and an organic solvent, the colorant is transferred to the resin side, and the water and organic solvent components are removed. This method is preferably used because the wet cake of the colorant can be used as is, and there is no need to dry it. In addition, a high-shear dispersion device such as a three-roll mill is preferably used to mix and knead the above-mentioned mixture.
[0076] [Release agent] The release agent is not particularly limited and can be appropriately selected from known ones. For example, waxes can be used as the release agent. Examples of the waxes include natural waxes such as vegetable waxes such as carnauba wax, cotton wax, and wood wax rice wax; animal waxes such as beeswax and lanolin; mineral waxes such as ozokerite and cerusine; and petroleum waxes such as paraffin, microcrystalline, and petrolatum.
[0077] As the release agent, in addition to these natural waxes, synthetic hydrocarbon waxes such as Fischer-Tropsch wax, polyethylene, and polypropylene; synthetic waxes such as esters, ketones, and ethers; and the like can be used.
[0078] Further, as the release agent, in addition to the above-mentioned waxes, fatty acid amide compounds such as 12-hydroxystearic acid amide, stearic acid amide, phthalimide anhydride, and chlorinated hydrocarbons; homopolymers or copolymers of polyacrylates such as poly-n-stearyl methacrylate and poly-n-lauryl methacrylate, which are low molecular weight crystalline polymer resins (for example, copolymers of n-stearyl acrylate and ethyl methacrylate); and crystalline polymers having long alkyl groups in their side chains.
[0079] These release agents may be used alone or in combination of two or more.
[0080] The melting point of the release agent is not particularly limited, but is preferably 60° C. or more and 80° C. or less. When the melting point of the release agent is 60° C. or more, the release agent can be prevented from melting at low temperatures, and the heat-resistant storage stability can be prevented from decreasing. When the melting point of the release agent is 80° C. or more, when the resin melts and is in the fixing temperature range, the release agent can be prevented from melting sufficiently, which can prevent fixing offset from occurring, and can prevent image defects from occurring.
[0081] [Charge control agent] The charge control agent is not particularly limited and can be appropriately selected depending on the purpose.
[0082] Examples of the charge control agent include nigrosine dyes, triphenylmethane dyes, chromium-containing metal complex dyes, molybdic acid chelate pigments, rhodamine dyes, alkoxy amines, quaternary ammonium salts (including fluorine-modified quaternary ammonium salts), alkylamides, phosphorus simple substances or compounds, tungsten simple substances or compounds, fluorine-based activators, metal salicylic acid salts, and metal salts of salicylic acid derivatives.
[0083] Specific examples include the nigrosine dye Bontron 03, the quaternary ammonium salt Bontron P-51, the metal-containing azo dye Bontron S-34, the oxynaphthoic acid metal complex E-82, the salicylic acid metal complex E-84, and the phenol condensate E-89 (all manufactured by Orient Chemical Industry Co., Ltd.), the quaternary ammonium salt molybdenum complexes TP-302 and TP-415 (all manufactured by Hodogaya Chemical Co., Ltd.), LRA-901, the boron complex LR-147 (all manufactured by Nippon Carlit Co., Ltd.), copper phthalocyanine, perylene, quinacridone, azo pigments, and other polymeric compounds having functional groups such as sulfonic acid groups, carboxyl groups, and quaternary ammonium salts.
[0084] These charge control agents may be used alone or in combination of two or more.
[0085] The content of the charge control agent is not particularly limited and can be appropriately selected depending on the purpose. The content of the charge control agent is preferably 0.1% by mass to 10% by mass, more preferably 0.2% by mass to 5% by mass, based on the toner.
[0086] When the content of the charge control agent is 0.1% by mass or more and 10% by mass or less, the chargeability of the toner can be prevented from becoming too high, the effect of the main charge control agent can be maintained, the electrostatic attraction force with the developing roller can be prevented from increasing, and a decrease in the fluidity of the developer and a decrease in image density can be suppressed.
[0087] These charge control agents can be melt-kneaded together with the master batch and the resin and then dissolved and dispersed. Alternatively, they may be added when directly dissolved or dispersed in an organic solvent. Furthermore, they may be fixed on the toner surface after the toner particles are produced.
[0088] [External additives] As the external additive, inorganic fine particles or hydrophobically treated inorganic fine particles can be used in addition to the oxide fine particles.
[0089] Here, the hydrophobized inorganic fine particles are preferably inorganic fine particles having an average primary particle diameter of 1 nm to 100 nm, more preferably 5 nm to 70 nm. The average particle diameter indicates the volume average particle diameter measured using a laser diffraction / scattering type particle size distribution analyzer (LA-920, manufactured by HORIBA).
[0090] Moreover, the external additive preferably contains at least one type of hydrophobic inorganic fine particles having an average particle size as primary particles of 20 nm or less, and at least one type of inorganic fine particles having an average particle size of 30 nm or more.
[0091] The specific surface area of the external additive is 20m 2 / g~500m 2 The specific surface area is preferably 1 / g. The specific surface area is measured by a nitrogen gas adsorption BET method using a specific surface area measuring device.
[0092] The external additive is not particularly limited and can be appropriately selected according to purpose.External additives include, for example, silica fine particles, hydrophobic silica, fatty acid metal salts (e.g., zinc stearate, aluminum stearate, etc.), metal oxides (e.g., titania, alumina, tin oxide, antimony oxide, etc.), fluoropolymers, etc.Suitable additives include hydrophobized silica, titania, titanium oxide, and alumina fine particles.
[0093] Examples of silica fine particles include R972, R974, RX200, RY200, R202, R805, and R812 (all manufactured by Nippon Aerosil Co., Ltd.).
[0094] Examples of titania microparticles include P-25 (manufactured by Nippon Aerosil Co., Ltd.), STT-30, STT-65C-S (all manufactured by Titanium Kogyo Co., Ltd.), TAF-140 (manufactured by Fuji Titanium Kogyo Co., Ltd.), MT-150W, MT-500B, MT-600B, MT-150A (all manufactured by Teika Corporation).
[0095] Examples of hydrophobically treated titanium oxide particles include T-805 (manufactured by Nippon Aerosil Co., Ltd.), STT-30A, STT-65S-S (all manufactured by Titanium Kogyo Co., Ltd.), TAF-500T, TAF-1500T (all manufactured by Fuji Titanium Kogyo Co., Ltd.), MT-100S, MT-100T (all manufactured by Teika Corporation), and IT-S (manufactured by Ishihara Sangyo Co., Ltd.).
[0096] Hydrophobized oxide microparticles, hydrophobized silica microparticles, hydrophobized titania microparticles, and hydrophobized alumina microparticles can be obtained, for example, by treating hydrophilic microparticles with a silane coupling agent such as methyltrimethoxysilane, methyltriethoxysilane, or octyltrimethoxysilane.
[0097] Also suitable are silicone oil-treated oxide fine particles and inorganic fine particles, which are obtained by treating silicone oil with heat as necessary to form inorganic fine particles.
[0098] Examples of silicone oils include dimethyl silicone oil, methylphenyl silicone oil, chlorophenyl silicone oil, methylhydrogen silicone oil, alkyl-modified silicone oil, fluorine-modified silicone oil, polyether-modified silicone oil, alcohol-modified silicone oil, amino-modified silicone oil, epoxy-modified silicone oil, epoxy-polyether-modified silicone oil, phenol-modified silicone oil, carboxyl-modified silicone oil, mercapto-modified silicone oil, methacryl-modified silicone oil, and α-methylstyrene-modified silicone oil.
[0099] Examples of inorganic fine particles include silica, alumina, titanium oxide, barium titanate, magnesium titanate, calcium titanate, strontium titanate, iron oxide, copper oxide, zinc oxide, tin oxide, silica sand, clay, mica, wollastonite, diatomaceous earth, chromium oxide, cerium oxide, red iron oxide, antimony trioxide, magnesium oxide, zirconium oxide, barium sulfate, barium carbonate, calcium carbonate, silicon carbide, silicon nitride, etc. Among these, silica and titanium dioxide are particularly preferred.
[0100] These external additives may be used alone or in combination of two or more kinds.
[0101] The content of the external additive is not particularly limited and can be appropriately selected depending on the purpose. The content of the external additive is preferably 0.1% by mass to 5% by mass, more preferably 0.3% by mass to 3% by mass, based on the toner.
[0102] The average particle size of the inorganic fine particles as primary particles is not particularly limited, but is preferably 100 nm or less, more preferably 3 nm or more and 70 nm or less. If the average particle size is 3 nm or more, it is possible to prevent the inorganic fine particles from being buried in the toner and from not effectively exerting their functions. Also, if the average particle size is 100 nm or less, it is possible to prevent the photoconductor surface from being unevenly damaged.
[0103] [Glass transition temperature] The glass transition point (Tg) of the toner according to this embodiment is usually 40° C. or higher and 70° C. or lower, and preferably 45° C. or higher and 55° C. or lower. If it is 40° C. or higher, the heat-resistant storage stability of the toner is good, and if it is 70° C. or lower, the low-temperature fixing property is sufficient. Due to the coexistence of a crosslinked and / or elongated polyester resin, the toner according to this embodiment exhibits good storage stability even though it has a lower glass transition point than known polyester toners.
[0104] [viscosity] The viscosity of the toner according to this embodiment is usually 180° C. or less, preferably 90° C. or more and 160° C. or less, at a temperature (Tη) at which the viscosity becomes 1000 poise at a measurement frequency of 20 Hz. If the temperature exceeds 180° C., the low-temperature fixing property deteriorates. That is, from the viewpoint of achieving both low-temperature fixing property and hot offset resistance, TG′ is preferably higher than Tη.
[0105] In other words, the difference between TG' and Tη (TG'-Tη) is preferably 0° C. or more, more preferably 10° C. or more, and further preferably 20° C. or more. There is no particular upper limit to the difference.
[0106] From the viewpoint of achieving both heat-resistant storage stability and low-temperature fixability, the difference between Tη and Tg is preferably 0° C. or more and 100° C. or less, more preferably 10° C. or more and 90° C. or less, and particularly preferably 20° C. or more and 80° C. or less. The acid value of the toner according to this embodiment is more preferably 7 mg / g or more in order to prepare fine particles by a phase inversion emulsification method, and is preferably 30 mg / g or more in terms of metal crosslinking with the coagulated salt.
[0107] [Storage modulus] The storage modulus of the toner according to this embodiment is a temperature (TG′) at which the toner becomes 10,000 dyne / cm2 at a measurement frequency of 20 Hz, which is usually 100° C. or higher, and preferably 110° C. or higher and 200° C. or lower. If the storage modulus is lower than 100° C., the hot offset resistance is deteriorated.
[0108] In this specification, the storage modulus refers to a value (storage modulus G') measured using a dynamic viscoelasticity measuring device (rheometer) (ARES, manufactured by TA Instruments). Measurement of the storage modulus using a rheometer can be carried out as follows.
[0109] First, the toner is molded into pellets with a diameter of 8 mm and a thickness of 2 mm, which are then fixed to a parallel plate with a diameter of 8 mm and stabilized at 50°C. Next, under conditions of a frequency of 10 Hz (6.28 rad / s), a distortion of 0.1% (distortion control mode), a temperature rise rate of 2.0°C / m, and the toner pellets with a diameter of 8 mm and a thickness of 2 mm are fixed to a parallel plate with a diameter of 8 mm and stabilized at 50°C.
[0110] Next, the temperature is raised to 100°C at a heating rate of 2.0°C / min under conditions of a frequency of 10 Hz (6.28 rad / s) and a strain of 0.1% (strain control mode), and then the storage modulus G' (Pa) is measured with a strain of 1% and a cooling rate of 10°C / min.
[0111] The toner according to this embodiment has a maximum value in the measurement curve of storage modulus G' in dynamic viscoelasticity measurement in the range of 100° C. or higher. Specifically, in the viscoelasticity characteristics of the toner according to this embodiment relative to temperature change obtained by a viscoelasticity measuring device, the measurement curve of storage modulus G' has an inflection point at which the curve transitions from an upward convex to a downward convex, and the inflection point appears at the highest temperature at 100° C. or higher.
[0112] The inflection points in this embodiment are shown in Figure 1. In Figure 1, two inflection points are shown in the measurement curve of the storage modulus G' (inflection points (1) and (2)).
[0113] Regarding the inflection point (1), the storage modulus G' starts to decrease from a measurement temperature of about 40° C., and the rate of decrease becomes gentler at about 110° C. The point showing the maximum rate of decrease during the decrease (the point where the slope of the tangent to the measurement curve becomes horizontal) is the inflection point (1).
[0114] Regarding the inflection point (2), the storage modulus G' increases from a measurement temperature of about 120° C., and the rate of increase becomes gentler at about 150° C. The point showing the maximum rate of increase during the increase (the point where the slope of the tangent to the measurement curve becomes horizontal) is the inflection point (2).
[0115] In this embodiment, as shown in FIG. 1, when the storage modulus G' has a maximum value (inflection point (2)) in the range of 100° C. or higher, a toner having sufficient offset resistance and color reproducibility can be obtained.
[0116] In addition, the toner according to the present embodiment preferably has two extreme values in a measurement curve of the storage modulus G' in a range of 100° C. or higher. Specifically, as shown in FIG 1, the measurement curve of the storage modulus G' has a downwardly convex inflection point (1) and an upwardly convex inflection point (2) in a range of 100° C. or higher.
[0117] In this embodiment, the measurement curve of the storage modulus G' has two extreme values (inflection point (1) and inflection point (2)) in the range of 100° C. or higher, so that the offset resistance of the toner can be improved.
[0118] In addition, in the toner according to the present embodiment, the storage modulus G' is 1.0×10 3 More preferably, the storage modulus G' in the range of 100° C. or higher is 1.0×10 Pa or more. 3 Pa or more 1.0×10 5 The values are in the range of Pa or less.
[0119] In this embodiment, the storage modulus G' is 1.0×10 3 By setting the pressure drop at 0.5 Pa or more, the offset resistance of the toner can be further improved.
[0120] It is more preferable that the toner of this embodiment has two extreme values in the measurement curve of the storage modulus G' in the range of 110° C. to 160° C. Specifically, as shown in FIG 1, an inflection point (1) in the measurement curve of the storage modulus G' appears in the range of 110° C. to 140° C., and an inflection point (1) in the measurement curve of the storage modulus G' appears in the range of 140° C. to 160° C.
[0121] In this embodiment, the measurement curve of the storage modulus G' thus has two extreme values in the range of 110° C. or more and 160° C. or less, so that color reproducibility can be improved.
[0122] The toner of the present embodiment has a storage modulus G' of 1.0×10 4 When the storage modulus G' is 1.0×10 Pa, it is more preferable that the measurement temperature in the dynamic viscoelasticity measurement is 90° C. or higher. Specifically, as shown in FIG. 4 The temperature range that satisfies Pa is 90°C or higher.
[0123] In this embodiment, the storage elastic modulus G′ is 1.0×10 4 When the dynamic viscoelasticity is measured at a temperature of 90° C. or higher, the color reproducibility can be further improved.
[0124] <Toner storage unit> The toner storage unit according to the present embodiment stores the above-mentioned toner. In this specification, the toner storage unit is a unit having a function of storing toner and storing the toner. Examples of the toner storage unit include a toner storage container, a developing unit, a process cartridge, and the like.
[0125] The toner storage container is a container that stores toner.
[0126] The developer includes a means for containing and developing the toner.
[0127] The process cartridge is a cartridge that integrates at least an image carrier and a developing unit, contains toner, and is detachably mountable to an image forming apparatus. The process cartridge may further include at least one selected from a charging unit, an exposure unit, and a cleaning unit. A specific example of the process cartridge that constitutes a part of the toner storage unit of this embodiment is shown in FIG. 5 described later.
[0128] In the toner storage unit of the present embodiment, the above-mentioned toner is used, and thus the effects obtained by the above-mentioned toner can be obtained as is. Specifically, by mounting the toner storage unit of the present embodiment on an image forming apparatus and forming an image, the above-mentioned toner is used to form an image, and therefore the offset resistance and color reproducibility of the toner can be improved.
[0129] <Image forming device> The image forming apparatus according to this embodiment includes a photoconductor, a charging unit which charges the photoconductor, an exposure unit which exposes the charged photoconductor to light to form an electrostatic latent image, a developing unit which develops the electrostatic latent image formed on the photoconductor using the above-mentioned toner to form a toner image, a transfer unit which transfers the toner image formed on the photoconductor to a recording medium, and a fixing unit which fixes the toner image transferred to the recording medium.
[0130] Specifically, the image forming apparatus according to this embodiment can be configured as an example of the image forming apparatus according to this embodiment shown in FIG.
[0131] In FIG. 2, the image forming apparatus 100A has a photosensitive drum 10, a charging roller 20, an exposure device (not shown), developing devices 45 (K, Y, M, C), an intermediate transfer belt 50, a cleaning device 60 having a cleaning blade, and a discharge lamp 70.
[0132] The intermediate transfer belt 50 is supported by three rollers 51 arranged on the inside and can move in the direction of the arrow. Some of the three rollers 51 also function as transfer bias rollers that can apply a predetermined transfer bias to the intermediate transfer belt 50.
[0133] A cleaning device 90 having a cleaning blade is disposed near the intermediate transfer belt 50. A transfer roller 80 capable of applying a transfer bias for transferring a toner image onto the recording paper P is disposed opposite the intermediate transfer belt 50.
[0134] In addition, a corona charger 52 that applies an electric charge to the toner image on the intermediate transfer belt 50 is disposed around the intermediate transfer belt 50, between the contact portion between the photosensitive drum 10 and the intermediate transfer belt 50 and the contact portion between the intermediate transfer belt 50 and the recording paper P.
[0135] The developing devices 45 for each color, black (K), yellow (Y), magenta (M) and cyan (C), are equipped with a developer container 42 (K, Y, M, C), a developer supply roller 43 (K, Y, M, C), and a developing roller 44 (K, Y, M, C).
[0136] In the image forming apparatus 100A, the photoconductor drum 10 is uniformly charged by the charging roller 20, and then the exposure device (not shown) irradiates the photoconductor drum 10 with exposure light L to form an electrostatic latent image. Next, the electrostatic latent image formed on the photoconductor drum 10 is developed by supplying a developer (containing the above-mentioned toner) from the developing device 45 to form a toner image, and then the toner image is transferred onto the intermediate transfer belt 50 by a transfer bias applied from the roller 51.
[0137] Furthermore, the toner image on the intermediate transfer belt 50 is charged by a corona charger 52, and then transferred onto the recording paper P. Any toner remaining on the photoconductor drum 10 is removed by a cleaning device 60, and the photoconductor drum 10 is temporarily neutralized by a neutralization lamp 70.
[0138] In the image forming apparatus 100A shown in FIG. 2, the photoconductor drum 10, the charging roller 20, the exposure device, the developing device 45, the intermediate transfer belt 50, and the transfer roller 80 are examples of the photoconductor, the charging section, the exposure section, the developing section, the transfer section, and the fixing section, respectively, in the image forming apparatus of this embodiment.
[0139] FIG. 3 shows another example of an image forming apparatus.
[0140] In FIG. 3, image forming apparatus 100B is a tandem type color image forming apparatus, and includes a copying machine main body 150, a paper feed table 200, a scanner 300, and an automatic document feeder (ADF) 400.
[0141] In the copying machine main body 150, an intermediate transfer belt 50 is disposed in the center.
[0142] The intermediate transfer belt 50 is supported by rollers 14, 15, and 16, and can rotate in the direction of the arrow.
[0143] A cleaning device 17 that removes toner remaining on the intermediate transfer belt 50 is disposed near the support roller 15. In addition, four image forming units 120 of black (K), yellow (Y), magenta (M) and cyan (C) are disposed facing the intermediate transfer belt 50 supported by the rollers 14 and 15 along the conveying direction.
[0144] As shown in Figures 3 and 4, each image forming unit 120 for each color includes a photosensitive drum 10, a charging roller 20 for uniformly charging the photosensitive drum 10, a developing device 61 for forming a toner image, a transfer roller 62 for transferring the toner image for each color onto the intermediate transfer belt 50, a cleaning device 63, and a de-electrification lamp 64.
[0145] In addition, in the developing device 61 of the image forming unit 120, a toner image is formed by developing the electrostatic latent image formed on the photosensitive drum 10 (K, Y, M, C) with developers (containing the above-mentioned toners) of each color of black (K), yellow (Y), magenta (M) and cyan (C).
[0146] Further, an exposure device 21 is disposed near the image forming unit 120. The exposure device 21 irradiates the photoconductor drum 10 with exposure light L to form an electrostatic latent image.
[0147] Furthermore, a transfer device 22 is disposed on the side of the intermediate transfer belt 50 opposite to the side where the image forming unit 120 is disposed. The transfer device 22 is a transfer belt 24 supported by a pair of rollers 23, and the recording paper transported on the transfer belt 24 and the intermediate transfer belt 50 can come into contact with each other.
[0148] 3, a fixing device 25 is provided near the transfer device 22. The fixing device 25 has a fixing belt and a pressure roller 27 that is arranged to be pressed against the fixing belt .
[0149] Further, near the transfer device 22 and the fixing device 25, there is provided a reversing device 28 that reverses the recording paper in order to form images on both sides of the recording paper.
[0150] Next, a description will be given of the formation of a full-color image in the image forming apparatus 100B. First, an original is set on the original table 130 of the automatic document feeder (ADF) 400, or the automatic document feeder 400 is opened and an original is set on the contact glass 32 of the scanner 300, and the automatic document feeder 400 is closed.
[0151] Next, when a start switch (not shown) is pressed, when an original is set on the automatic original transport device 400, the original is transported and moved onto the contact glass 32, and when the original is set on the contact glass 32, the scanner 300 is immediately driven and the first traveling body 33 and the second traveling body 34 start to move.
[0152] At this time, light from the light source is irradiated by the first traveling body 33, and the reflected light from the document surface is reflected by a mirror on the second traveling body 34 and received by the reading sensor 36 through an imaging lens 35. In this way, the color document (color image) is read, and image information of each color of black, yellow, magenta, and cyan is obtained.
[0153] Furthermore, after an electrostatic latent image of each color is formed on the photoconductor drum 10 by the exposure device 21 based on the obtained image information of each color, the electrostatic latent image of each color is developed with a developer (containing the above-mentioned toner) supplied from the image forming unit 120 of each color to form a toner image of that color. The toner images of each color are transferred in sequence onto the intermediate transfer belt 50 rotated by rollers 14, 15, and 16, and a composite toner image is formed on the intermediate transfer belt 50.
[0154] In the paper feed table 200, one of the paper feed rollers 142 is selectively rotated to feed recording paper from one of the paper feed cassettes 144 provided in multiple stages in a paper bank 143. The fed recording paper is then separated one by one by a separation roller 145 and sent to a paper feed path 146, and is transported by a transport roller 147 to a paper feed path 148 in the copying machine main body 150, where it is stopped by abutting against a registration roller 49.
[0155] Alternatively, recording paper is fed from manual feed tray 54, separated one by one by separation roller 58, and fed into manual feed path 53, where it is stopped by contacting registration roller 49. Registration roller 49 is generally grounded, but may be used with a bias applied to it in order to remove paper dust from the recording paper.
[0156] Then, the registration rollers 49 are rotated in synchronization with the composite toner image formed on the intermediate transfer belt 50, and the recording paper is sent between the intermediate transfer belt 50 and the transfer device 22, where the composite toner image is transferred onto the recording paper.
[0157] The recording paper onto which the composite toner image has been transferred is transported by transfer device 22 and sent to fixing device 25. In fixing device 25, the composite toner image is fixed onto the recording paper by heat and pressure applied by fixing belt 26 and pressure roller 27. Thereafter, the recording paper is switched by switching claw 55 and discharged by discharge rollers 56, and stacked on discharge tray 57.
[0158] Alternatively, the sheet is switched by a switching claw 55, inverted by the inverting device 28, and guided to the transfer position again, where an image is formed on the back side as well, and then discharged by discharge rollers 56 and stacked on a discharge tray 57.
[0159] Any toner remaining on the intermediate transfer belt 50 after the composite toner image has been transferred is removed by a cleaning device 17 .
[0160] In the image forming apparatus 100B shown in FIG. 3, the photoconductor drum 10, the charging roller 20, the exposure device 21, the image forming unit 120, the intermediate transfer belt 50, and the fixing device 25 are examples of the photoconductor, the charging section, the exposure section, the developing section, the transfer section, and the fixing section in the image forming apparatus of this embodiment.
[0161] FIG. 5 shows an example of a process cartridge as yet another example of an image forming apparatus.
[0162] The process cartridge 110 includes a photosensitive drum 10 , a corona charger 52 , a developing device 40 , a transfer roller 80 and a cleaning device 90 .
[0163] 5, in the process cartridge 110, an exposure device (not shown) irradiates the photoconductor drum 10, which has been uniformly charged by the corona charger 52, with exposure light L to form an electrostatic latent image. Next, the electrostatic latent image formed on the photoconductor drum 10 is developed by supplying a developer (containing the above-mentioned toner) from the developing device 40 to form a toner image, and then the toner image is formed on the photoconductor drum 10 by a transfer bias applied by the corona charger 52.
[0164] The toner image formed on the photosensitive drum 10 is transferred onto a recording paper P by a transfer roller 80. The toner remaining on the photosensitive drum 10 is removed by a cleaning device 90.
[0165] In the image forming apparatus 100B shown in Fig. 3, the photoconductor drum 10, the corona charger 52, the exposure device, and the developing device 40 are examples of the photoconductor, the charging unit, the exposure unit, and the developing unit in the image forming apparatus of this embodiment. The photoconductor drum 10 is also an example of the transfer unit in the image forming apparatus of this embodiment. Furthermore, the transfer roller 80 is an example of the fixing unit in the image forming apparatus of this embodiment.
[0166] In the image forming apparatus of the present embodiment, the above-mentioned toner is used, and thus the effects obtained by the above-mentioned toner can be obtained as is. Specifically, by using the image forming apparatus of the present embodiment, the above-mentioned toner is used to form an image, and therefore the offset resistance and color reproducibility of the toner in the image formation can be improved.
[0167] <Image forming method> The image forming method according to this embodiment includes a charging step of charging a photoreceptor, an exposure step of exposing the charged photoreceptor to light to form an electrostatic latent image, a developing step of developing the electrostatic latent image formed on the photoreceptor using the above-mentioned toner to form a toner image, a transfer step of transferring the toner image formed on the photoreceptor to a recording medium, and a fixing step of fixing the toner image transferred to the recording medium.
[0168] The image forming method according to the present embodiment is realized by implementing each of the examples of the image forming apparatuses shown in the above-mentioned FIGS.
[0169] Specifically, in the image forming apparatus 100A in Fig. 2 and the image forming apparatus 100B in Fig. 3, the charging step is performed by the photoconductor drum 10 and the charging roller 20, respectively, to charge the photoconductor. In the process cartridge 110 in Fig. 5, the charging step is performed by the photoconductor drum 10 and the corona charger 52 to charge the photoconductor.
[0170] The exposure step is performed by the respective exposure devices in the image forming apparatus 100A in Fig. 2 and the process cartridge 110 in Fig. 5, where an electrostatic latent image is formed by exposing a charged photoconductor to light. Also, in the image forming apparatus 100B in Fig. 3, the exposure step is performed by the exposure device 21, where an electrostatic latent image is formed by exposing a charged photoconductor to light.
[0171] In the image forming apparatus 100A of Fig. 2, the developing step is performed by the developing device 45, where the electrostatic latent image formed on the photoconductor is developed with the above-mentioned toner to form a toner image. In the image forming apparatus 100B of Fig. 3, the developing step is performed by the image forming unit 120. Furthermore, in the process cartridge 110 of Fig. 5, the developing step is performed by the developing device 40, where the electrostatic latent image formed on the photoconductor is developed with the above-mentioned toner to form a toner image.
[0172] In the image forming apparatus 100A in Fig. 2 and the image forming apparatus 100B in Fig. 3, the transfer step is performed by the intermediate transfer belt 50, and the toner image formed on the photoconductor is transferred to a recording medium. In the process cartridge 110 in Fig. 5, the transfer step is performed by the photoconductor drum 10, and the toner image formed on the photoconductor is transferred to a recording medium.
[0173] The fixing step is performed by the transfer roller 80 in the image forming apparatus 100A in Fig. 2 and the process cartridge 110 in Fig. 5, and the transferred toner image is fixed to the recording medium. Also, in the image forming apparatus 100B in Fig. 3, the fixing step is performed by the fixing device 25, and the transferred toner image is fixed to the recording medium.
[0174] In the image forming method of the present embodiment, the above-mentioned toner is used, and thus the effects obtained by the above-mentioned toner can be obtained as is. Specifically, by using the image forming method of the present embodiment, the above-mentioned toner is used to form an image, and therefore the offset resistance and color reproducibility of the toner in the image formation can be improved. EXAMPLES
[0175] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples. In the following, "parts" and "%" are by weight unless otherwise specified.
[0176] [Preparation of toner in Example 1] (Synthesis of amorphous polyester resin 1) In a reaction vessel equipped with a cooling tube, a stirrer and a nitrogen inlet tube, 562 parts of bisphenol A ethylene oxide 2 mole adduct, 75 parts of bisphenol A propylene oxide 2 mole adduct, 87 parts of bisphenol A propylene oxide 3 mole adduct, 143 parts of terephthalic acid, 126 parts of adipic acid and 2 parts of dibutyltin oxide were put and reacted at 230 ° C. and normal pressure for 8 hours, and further reacted at a reduced pressure of 10 to 15 mmHg for 5 hours, after which 69 parts of trimellitic anhydride were put into the reaction vessel and reacted at 180 ° C. and normal pressure for 2 hours to obtain amorphous polyester resin 1. The acid value of amorphous polyester resin 1 was 40 mg KOH / g.
[0177] (Preparation of pigment master batch 1) Amorphous polyester resin 1 and Pigment Red 269 were premixed in a 1:1 ratio using a Henschel mixer (FM20B, manufactured by Mitsui Miike Chemical Engineering Co., Ltd.), and then melted and kneaded at a temperature of 130° C. using a twin-screw kneader (PCM-30, manufactured by Ikegai Co., Ltd.). The resulting kneaded product was rolled to a thickness of 2.7 mm using a roller, cooled to room temperature using a belt cooler, and coarsely pulverized to 200 μm to 300 μm using a hammer mill, to obtain pigment master batch 1.
[0178] (Synthesis of crystalline polyester resin 1) 1,6-hexanediol and sebacic acid were charged into a 5L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple so that the ratio of OH groups to COOH groups (OH / COOH) was 1.1. The mixture was reacted while draining water along with 500 ppm of titanium tetraisopropoxide relative to the mass of the charged raw materials, and finally heated to 235°C and reacted for 1 hour. Then, the mixture was reacted for 6 hours under a reduced pressure of 10 mmHg or less. The temperature was then set to 185°C, and trimellitic anhydride was added so that the molar ratio with COOH groups was 0.053, and the mixture was reacted for 2 hours with stirring to obtain a crystalline polyester resin 1.
[0179] (Preparation of Crystalline Polyester Resin Dispersion 1) Crystalline polyester resin 1 (55 parts), methyl ethyl ketone (35 parts), and 2-propyl alcohol (10 parts) were added to a four-neck flask. Then, the mixture was stirred while being heated at the melting point temperature of the crystalline polyester resin 1 to dissolve the crystalline polyester resin 1. Then, a 28% by mass aqueous ammonia solution was added so that the neutralization rate was 200%. The neutralization rate was calculated from the acid value of the crystalline polyester resin. Furthermore, ion-exchanged water (130 parts) was gradually added to carry out phase inversion emulsification, and then the solvent was removed. Then, ion-exchanged water was added to adjust the solid content concentration (concentration of crystalline polyester resin 1) to 25% by mass, and crystalline polyester resin dispersion 1, which is a binder resin dispersion for toner, was obtained.
[0180] (Production of wax emulsion 1) 28 parts of HNP-9 (manufactured by Nippon Seiro) as a wax and Sanisol B50 as a surfactant were added to 100 parts of ion-exchanged water. This was dispersed with a homogenizer while being heated to 90° C., to obtain Wax Emulsion 1. The solid content was 30%.
[0181] (Preparation of oil phase) Wax emulsion 1 (50 parts), non-crystalline polyester resin 1 (8,000 parts), crystalline polyester resin dispersion 1 (50 parts), and pigment master batch 1 (50 parts) were placed in a container and mixed with a TK homomixer (manufactured by Primix Corporation) at 5,000 rpm for 60 minutes to obtain oil phase 1. The above blend amounts indicate the blend amounts of solids in each raw material.
[0182] (Preparation of aqueous phase) 990 parts of water, 20 parts of sodium dodecyl sulfate, and 90 parts of ethyl acetate were mixed and stirred to obtain a milky white liquid. This was designated as aqueous phase 1.
[0183] (emulsification process) Oil phase 1 (700 parts) was added with 20 parts of 28% aqueous ammonia while stirring at 8,000 rpm using a TK homomixer, and mixed for 10 minutes. Then, aqueous phase 1 (1,200 parts) was gradually added dropwise to obtain emulsified slurry 1.
[0184] (Solvent removal process) The emulsified slurry 1 was placed in a vessel equipped with a stirrer and a thermometer, and the solvent was removed at 30° C. for 180 minutes to obtain a solvent-free slurry 1.
[0185] (agglomeration process) 100 parts of 3% magnesium chloride solution was added dropwise to the solvent-removed slurry 1 and stirred for 5 minutes, then the temperature was raised to 60°C. When the particle size reached 5.0 μm, 50 parts of sodium chloride was added to terminate the aggregation process, and aggregated slurry 1 was obtained.
[0186] (fusion process) The aggregated slurry 1 was heated to 70° C. while stirring, and cooled when the average circularity reached 0.957 to obtain a dispersed slurry 1. The average circularity was measured using a wet flow type particle size / shape analyzer and analysis software (FPIA (registered trademark)-2100 Data Processing Program for FPIA version 00-10, manufactured by Sysmex Corporation).
[0187] (Annealing process, cleaning process, drying process) Toner dispersion liquid 1 was stored at 45° C. for 10 hours, filtered under reduced pressure, and washed and dried as follows. (1) 100 parts of ion-exchanged water was added to the filter cake, mixed with a TK homomixer (at 12,000 rpm for 10 minutes), and then filtered. (2) 900 parts of ion-exchanged water was added to the filter cake of (1), and ultrasonic vibration was applied and mixed with a TK homomixer (rotation speed 12,000 rpm for 30 minutes), and then the mixture was filtered under reduced pressure. This operation was repeated until the electrical conductivity of the reslurry liquid became 10 μC / cm or less, and then the mixture was filtered to obtain filter cake 1. The filter cake 1 was dried in a circulating air dryer at 45° C. for 72 hours and sieved through a 75 μm mesh to obtain colored resin particles 1.
[0188] (External addition process) 2.5 parts of inorganic fine particles (TS530, manufactured by Cabosil) were added to 100 parts of colored resin particles 1, and mixed in a Henschel mixer at 40 m / s for 10 minutes to obtain toner 1. The ratio of aluminum to carboxyl groups in toner 1 calculated from the quantitative ICP analysis value was 33%.
[0189] [Preparation of toner in Example 2] Toner 2 was obtained in the same manner as in Example 1, except that the 3% magnesium chloride solution in the aggregation step was replaced with a 3% calcium chloride solution. The ratio of calcium to carboxyl groups in Toner 2 calculated from the quantitative ICP analysis value was 30%.
[0190] [Preparation of toner in Example 3] (Synthesis of amorphous polyester resin 2) In a reaction vessel equipped with a cooling tube, a stirrer and a nitrogen inlet tube, 562 parts of bisphenol A ethylene oxide 2 mole adduct, 75 parts of bisphenol A propylene oxide 2 mole adduct, 87 parts of bisphenol A propylene oxide 3 mole adduct, 143 parts of terephthalic acid, 126 parts of adipic acid and 2 parts of dibutyltin oxide were put and reacted at 230 ° C. and normal pressure for 8 hours, and further reacted at a reduced pressure of 10 to 15 mmHg for 5 hours, after which 69 parts of trimellitic anhydride were put into the reaction vessel and reacted at 180 ° C. and normal pressure for 2 hours to obtain amorphous polyester resin 2. The acid value of amorphous polyester resin 2 was 35 mg KOH / g.
[0191] (Preparation of pigment master batch 2) Amorphous polyester resin 2 and Pigment Red 269 were premixed in a 1:1 ratio using a Henschel mixer (FM20B, manufactured by Mitsui Miike Chemical Engineering Co., Ltd.), and then melted and kneaded at a temperature of 130° C. using a twin-screw kneader (PCM-30, manufactured by Ikegai Corporation). The resulting kneaded product was rolled to a thickness of 2.7 mm using a roller, cooled to room temperature using a belt cooler, and coarsely pulverized to 200 μm to 300 μm using a hammer mill, to obtain pigment master batch 2.
[0192] (Preparation of Oil Phase 2) Wax emulsion 1 (50 parts), polyester resin 1 (8,000 parts), crystalline polyester resin dispersion 1 (50 parts), and pigment master batch 2 (50 parts) were placed in a container and mixed with a TK homomixer (manufactured by Primix Corporation) at 5,000 rpm for 60 minutes to obtain oil phase 2.
[0193] (emulsification process) Oil phase 2 (700 parts) was added with 20 parts of 28% aqueous ammonia while stirring at 8,000 rpm using a TK homomixer, and mixed for 10 minutes. Then, aqueous phase 1 (1,200 parts) was gradually added dropwise to obtain emulsified slurry 2.
[0194] (Solvent removal process) The emulsified slurry 2 was placed in a vessel equipped with a stirrer and a thermometer, and the solvent was removed at 30° C. for 180 minutes, whereby a solvent-free slurry 2 was obtained.
[0195] (agglomeration process) 100 parts of 3% magnesium chloride solution was added dropwise to the solvent-removed slurry 2 and stirred for 5 minutes, then the temperature was raised to 60°C. When the particle size reached 5.0 μm, 50 parts of sodium chloride was added to terminate the aggregation process, and aggregated slurry 3 was obtained.
[0196] (fusion process) The aggregated slurry 3 was heated to 70° C. with stirring, and cooled when the average circularity reached 0.957, to obtain a dispersed slurry 3.
[0197] (Annealing process, cleaning process, drying process) Toner dispersion liquid 1 was stored at 45° C. for 10 hours, filtered under reduced pressure, and washed and dried as follows. (1) 100 parts of ion-exchanged water was added to the filter cake, mixed with a TK homomixer (at 12,000 rpm for 10 minutes), and then filtered. (2) 900 parts of ion-exchanged water was added to the filter cake of (1), and ultrasonic vibration was applied and mixed with a TK homomixer (rotation speed 12,000 rpm for 30 minutes), and then the mixture was filtered under reduced pressure. This operation was repeated until the electrical conductivity of the reslurry liquid became 10 μC / cm or less, and then the mixture was filtered to obtain filter cake 3. The filtered cake 3 was dried in a circulating air dryer at 45° C. for 72 hours and sieved through a 75 μm mesh to obtain colored resin particles 3.
[0198] (External addition process) 2.5 parts of inorganic fine particles (TS530, manufactured by Cabosil) were added to 100 parts of colored resin particles 3, and mixed in a Henschel mixer at 40 m / s for 10 minutes to obtain toner 3. The ratio of magnesium to carboxyl groups in toner 3, calculated from the quantitative ICP analysis value, was 28%.
[0199] [Preparation of toner in Example 4] (Synthesis of amorphous polyester resin 3) In a reaction vessel equipped with a cooling tube, a stirrer and a nitrogen inlet tube, 362 parts of bisphenol A ethylene oxide 2 mole adduct, 75 parts of bisphenol A propylene oxide 2 mole adduct, 83 parts of bisphenol A propylene oxide 2 mole adduct, 143 parts of terephthalic acid, 126 parts of adipic acid and 2 parts of dibutyltin oxide were put and reacted at 230°C and normal pressure for 8 hours, and further reacted at a reduced pressure of 10 to 15 mmHg for 5 hours, after which 69 parts of trimellitic anhydride were put into the reaction vessel and reacted at 180°C and normal pressure for 2 hours to obtain amorphous polyester resin 3. The acid value of amorphous polyester resin 3 was 30 mgKOH / g. Toner 4 was obtained in the same manner as in Example 1, except that amorphous polyester resin 1 was replaced with amorphous polyester resin 3. The ratio of magnesium to carboxyl groups in toner 4 calculated from the quantitative analysis value of ICP was 23%.
[0200] [Preparation of toner in Example 5] Toner 5 was obtained in the same manner as in Example 4, except that amorphous polyester resin 1 was replaced with amorphous polyester resin 3, and magnesium sulfate was used instead of magnesium chloride in the aggregation step. The ratio of magnesium to carboxyl groups in toner 5 calculated from the quantitative ICP analysis value was 20%.
[0201] [Preparation of toner in Comparative Example 1] (Synthesis of amorphous polyester resin 4) In a reaction vessel equipped with a cooling tube, a stirrer and a nitrogen inlet tube, 255 parts of bisphenol A ethylene oxide 2 mole adduct, 480 parts of bisphenol A propylene oxide 2 mole adduct, 223 parts of terephthalic acid, 49 parts of adipic acid and 2 parts of dibutyltin oxide were placed and reacted at 230°C and normal pressure for 8 hours, and further reacted at a reduced pressure of 10 to 15 mmHg for 5 hours. Then, 1 part of trimellitic anhydride was placed in the reaction vessel and reacted at 180°C and normal pressure for 2 hours to obtain amorphous polyester resin 3. The acid value of amorphous polyester resin 3 was 10 mgKOH / g. Toner 6 was obtained in the same manner as in Example 1, except that amorphous polyester resin 1 was replaced with amorphous polyester resin 4. The ratio of magnesium to carboxyl groups in toner 6 calculated from the quantitative analysis value of ICP was 16%.
[0202] [Preparation of toner in Comparative Example 2] (Preparation of aqueous phase) 963 parts of water, 37 parts of a 48.3% aqueous solution of sodium dodecyldiphenyletherdisulfonate (Eleminol (registered trademark) MON-7, manufactured by Sanyo Chemical Industries, Ltd.), and 90 parts of ethyl acetate were mixed and stirred to obtain a milky white liquid. This was used as aqueous phase 2.
[0203] (Synthesis of non-crystalline intermediate polyester) In a reaction vessel equipped with a cooling tube, a stirrer and a nitrogen inlet tube, 200 parts of bisphenol A ethylene oxide 2 mole adduct, 563 parts of bisphenol A propylene oxide 2 mole adduct, 283 parts of terephthalic acid, 22 parts of trimellitic anhydride and 2 parts of dibutyltin oxide were placed and reacted at 230°C and normal pressure for 7 hours, and further reacted at a reduced pressure of 10 to 15 mmHg for 5 hours to obtain a non-crystalline intermediate polyester 1. Next, in a reaction vessel equipped with a cooling tube, a stirrer and a nitrogen inlet tube, non-crystalline intermediate polyester 1 (410 parts), 89 parts of isophorone diisocyanate and 500 parts of ethyl acetate were placed and reacted at 100°C for 5 hours to obtain a prepolymer 1.
[0204] (Synthesis of ketimine compounds) Into a reaction vessel equipped with a stirring bar and a thermometer, 170 parts of isophoronediamine and 75 parts of methyl ethyl ketone were charged and reacted at 45° C. for 5.5 hours to obtain Ketimine Compound 1.
[0205] (Synthesis of crystalline polyester resin) 248 g of stearic acid, 27 g of ethylene glycol, and 0.5 g of titanium dihydroxybis(triethanolamine) as a condensation catalyst were placed in a reaction vessel equipped with a cooling tube, a thermometer, a stirrer, a dehydrator, and a nitrogen inlet tube, and the mixture was reacted for 2 hours under a nitrogen stream at 180°C while distilling off the water produced, and then further reacted for 3 hours under a reduced pressure of 5 to 20 mmHg to obtain crystalline polyester resin 1.
[0206] (Preparation of crystalline resin dispersant resin) In a 5L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer and a thermocouple, 6.0 parts of sebacic acid, 5.4 parts of ethylene glycol, 3.4 parts of fumaric acid and 9.9 parts of xylene were placed and reacted at 180°C for 10 hours, then heated to 200°C and reacted for 3 hours, and further reacted at a pressure of 8.3KPa for 2 hours. Next, a solution of 38.3 parts of styrene, 0.3 parts of methacrylic acid and 1.2 parts of di-t-butyl peroxide dissolved in 3.9 parts of xylene was dropped over 3 hours, and the mixture was kept at 170°C for 30 minutes, and the solvent was removed to obtain crystalline resin dispersant resin 1 for crystalline polyester.
[0207] (Preparation of crystalline polyester resin dispersion) Crystalline polyester resin 1 (446 parts), 1,894 parts of ethyl acetate, and 446 parts of crystalline resin dispersant resin were charged into a stirrable pressure vessel and stirred mechanically at 180 rpm for 4 hours. Carbon dioxide was then passed as a supercritical fluid at 150°C, 60 MPa, and a flow rate of 5.0 L / min (standard condition equivalent) so that the volume ratio of carbon dioxide was 85%. A mixture of crystalline polyester resin and supercritical carbon dioxide was prepared, and crystalline polyester resin dispersion 1 was obtained.
[0208] (Preparation of oil phase) In a container equipped with a stirring rod and a thermometer, 120 parts of paraffin wax (melting point 90°C), 446 parts of crystalline polyester resin dispersion 1, and 1894 parts of ethyl acetate were charged, and the mixture was heated to 80°C under stirring, and then kept at 80°C for 5 hours, and then cooled to 30°C in 1 hour. Next, 250 parts of cyan pigment (CI Pigment Blue 15:3) and 1000 parts of ethyl acetate were charged in the container and mixed for 1 hour to obtain raw material solution 1. Raw material solution 1 (1324 parts) was transferred to the container, and the pigment and wax were dispersed using a bead mill (Ultraviscomill, manufactured by Imex Co., Ltd.) under the conditions of a liquid delivery speed of 1 kg / hr, a disk peripheral speed of 6 m / sec, 80% by volume of 0.5 mm zirconia beads, and 5 passes to obtain pigment-wax dispersion 1.
[0209] (Emulsification and desolvation) Pigment-wax dispersion 1 (375 parts), prepolymer 1 (500 parts), and ketimine compound 1 (15 parts) were placed in a container and mixed for 5 minutes at 5000 rpm using a TK homomixer (manufactured by Tokushu Kika Co., Ltd.), then water phase 1 (1200 parts) was added to the container and mixed for 1.5 hours at 10000 rpm using a TK homomixer to obtain emulsion slurry 1. Emulsion slurry 1 was placed in a container equipped with a stirrer and thermometer, and the solvent was removed at 30°C for 8 hours, and then aged at 40°C for 72 hours to obtain dispersion slurry 1.
[0210] (Washing and drying) Dispersion slurry 1 (100 parts) was filtered under reduced pressure, and the following series of washing treatments were performed. That is, 100 parts of ion-exchanged water was added to the obtained filter cake, and the mixture was mixed with a TK homomixer (at a rotation speed of 12000 rpm for 10 minutes), and then filtered. 100 parts of 10% hydrochloric acid was added to the obtained filter cake, and the mixture was mixed with a TK homomixer (at a rotation speed of 12000 rpm for 10 minutes), and then filtered. 300 parts of ion-exchanged water was added to the obtained filter cake, and the mixture was mixed with a TK homomixer (at a rotation speed of 12000 rpm for 10 minutes), and then filtered twice to obtain filter cake 1. This filter cake 1 was dried at 45°C for 48 hours using a circulating dryer, and then sieved with a 75 μm mesh to obtain toner base particles 1. Next, 2.20% by mass of large particle silica (HSP160A manufactured by Fuso Chemical Industry Co., Ltd. and RX40 manufactured by Nippon Aerosil Co., Ltd.) was added to the obtained toner base particles 1, and mixed with a Henschel mixer. Further, 0.6 parts by mass of hydrophobic small particle silica (R972, manufactured by Nippon Aerosil Co., Ltd.) was mixed in a Henschel mixer, and coarse particles were removed using a screen with an opening of 37 μm to prepare Toner 7. The ratio of metal salt to carboxyl group in Toner 7 calculated from the quantitative analysis value of ICP was 0%.
[0211] [evaluation] (High temperature fixability (high temperature offset resistance)) Using the fixing unit of a color multifunction printer (RICOH Co., Ltd., imagio MP C4500), a 0.6 mg / cm2 solid black unfixed image was formed on plain paper and fixed at different fixing temperatures. The temperature at which hot offset occurred was measured and rated on a three-level scale. Excellent: 190℃ or higher Good: 170℃ or higher but less than 190℃ Not acceptable: below 170℃
[0212] (color reproducibility) Color reproducibility was evaluated using a colorimeter (a portable spectrophotometer manufactured by X-Rite939) under conditions of a D50 light source and a 2-degree visual field, measuring chroma C*, and rating it on a three-level scale. Excellent:78~81 Good: 75~78 Not acceptable: Less than 75
[0213] Table 1 shows various physical properties of the toners in the examples and comparative examples measured by the methods described above.
[0214] [Table 1]
[0215] As can be seen from Table 1, Examples 1 to 5 were excellent or good in both high temperature fixability and color reproducibility.
[0216] In contrast, the high temperature fixability was poor in both Comparative Examples 1 and 2. Furthermore, the color reproducibility in Comparative Example 2 was also poor.
[0217] From these results, it is found that a toner which contains a binder resin and a metal crosslinking agent which forms a metal bridge with the binder resin, and in which the measurement curve of the storage modulus G' in dynamic viscoelasticity measurement has a maximum value in the range of 100°C or more, has excellent offset resistance and color reproducibility.
[0218] Although an embodiment of the present invention has been described above, the present invention is not limited to a specific embodiment, and various modifications and changes are possible within the scope of the invention described in the claims. [Explanation of symbols]
[0219] 100A, 100B Image forming apparatus 110 Process cartridge 120 Image forming unit 130 Manuscript stand 142 Paper feed roller 143 Paper Bank 144 Paper feed cassette 145 Separation roller 146, 148 Paper feed path 147 Transport roller 150 Copying machine body 200 Paper feed table 300 Scanner 400 Automatic Document Feeder (ADF) 10 (K, Y, M, C) Photoconductor drum 14, 15, 16 Laura 17, 60, 63, 90 Cleaning device 20 Charging roller 20 21 Exposure equipment 22 Transcription device 23 Laura 24 Transfer belt 25 Fixing device 26 Fixing belt 27 Pressure roller 28 Reversing device 32 Contact Glass 33 First Running Body 34 Second Running Body 35 Imaging Lens 36 Reading sensor 40 Developer 42 (K, Y, M, C) Developer container 43 (K, Y, M, C) Developer supply roller 44 (K, Y, M, C) Developing roller 45(K, Y, M, C) developer 49 Registration roller 50 Intermediate transfer belt 51 Lola 52 Corona charger 53 Manual feed path 54 Manual feed tray 55 Switching claw 56 Discharge roller 57 Output tray 58 Separation roller 61 Developer 62, 80 Transfer roller 64, 70 Static electricity removal lamp L exposure light P Recording paper [Prior art documents] [Patent documents]
[0220] [Patent Document 1] JP 2005-49484 A [Patent Document 2] JP 2009-288805 A
Claims
1. A toner comprising a binder resin and a metal cross-linking agent that forms a metal bridge with the binder resin, The binder resin contains a crystalline polyester resin, the content of the crystalline polyester resin in the toner is 20% by mass or less, A toner, wherein a measurement curve of storage modulus G' in dynamic viscoelasticity measurement has a maximum value in the range of 100° C. or higher.
2. 2. The toner according to claim 1, wherein the measurement curve of the storage modulus G' has two extreme values in a range of 100° C. or higher.
3. The storage modulus G' is 1.0 x 10 3 The toner according to claim 1 or 2, wherein the viscosity is 100 Pa or more.
4. The toner according to claim 1, wherein the crystalline polyester resin is synthesized from an aliphatic dicarboxylic acid and an aliphatic diol.
5. The storage elastic modulus G' is 1.0×10 4 The toner according to claim 1 , wherein the dynamic viscoelasticity is measured at a measurement temperature of 90° C. or higher when the dynamic viscoelasticity is 100 Pa.
6. The toner according to claim 1 , wherein the metal crosslinking agent contains a monovalent or higher metal salt.
7. A toner storage unit containing the toner according to any one of claims 1 to 6.
8. A photoconductor; A charging unit that charges the photoconductor; an exposure section for exposing the charged photoconductor to light to form an electrostatic latent image; a developing section for developing the electrostatic latent image formed on the photoconductor with the toner according to claim 1 to form a toner image; a transfer section that transfers the toner image formed on the photoreceptor onto a recording medium; a fixing section for fixing the toner image transferred onto the recording medium.
9. a charging step of charging a photoconductor; an exposure step of exposing the charged photoconductor to light to form an electrostatic latent image; a developing step of developing the electrostatic latent image formed on the photoconductor with the toner according to claim 1 to form a toner image; a transfer step of transferring the toner image formed on the photoreceptor onto a recording medium; A fixing step of fixing the toner image transferred onto the recording medium.
Citation Information
Patent Citations
Yellow toner
JP2004170825A
Electrostatic charge image developing toner, method of manufacturing the same, and electrostatic charge image developer, and image forming method using the same
JP2004191927A
Toner and image forming apparatus using the same
JP2005049484A
Toner composition and method for production thereof
JP2009288805A
Toner for electrostatic charge image development
JP2010072476A